A mRNA determinant of gRNA-directed kinetoplastid editing - Kabb, Aaron L. (Oxford University Press, 2001)
Several mitochondrial mRNAs of the kinetoplastid protozoa do not encode a functional open reading frame until they have been edited through the addition or deletion of U nucleotides at specific sites. Genetic information specifying the location and extent of editing is present on guide RNAs (gRNAs). The sequence adjacent to most mRNA editing sites has a high purine content which previously has been proposed to facilitate the editing reaction through base-pairing to a poly(U) tail at the 3′ end of the gRNA. We demonstrate here that gRNA binding alone is insufficient to create an editing site and that the mRNA sequence near an editing site is an additional determinant affecting the efficiency of the reaction.